(untitled) (Revista Española de Estudios Agrosociales y Pesqueros, 2023)
This article aims to get insight about the history of the manufacture and consumption of pasta in Spain. Historically, pasta production was very small (mainly fideos noodles) and was concentrated in the east of the country. However, from the last third of the 19th century, pasta production (in small and semi-artisan factories) increased throughout the country. The majority of the factories were in Catalonia, although there were many in Andalusia and the Balearic Islands. After the Civil War, the manufacture and consumption of pasta increased again. From the second half of the 20th century, a process of production concentration in large companies that used industrial methods occurred, while many small and medium-sized companies vanished. In 2020, the four largest companies accounted for 90% of national pasta production, when in 1995 that percentage had been 68%. Currently, the large companies continue to maintain control, while the consumption of packaged fresh pasta has increased.